6(5+c)=5c-4

Simple and best practice solution for 6(5+c)=5c-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(5+c)=5c-4 equation:


Simplifying
6(5 + c) = 5c + -4
(5 * 6 + c * 6) = 5c + -4
(30 + 6c) = 5c + -4

Reorder the terms:
30 + 6c = -4 + 5c

Solving
30 + 6c = -4 + 5c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-5c' to each side of the equation.
30 + 6c + -5c = -4 + 5c + -5c

Combine like terms: 6c + -5c = 1c
30 + 1c = -4 + 5c + -5c

Combine like terms: 5c + -5c = 0
30 + 1c = -4 + 0
30 + 1c = -4

Add '-30' to each side of the equation.
30 + -30 + 1c = -4 + -30

Combine like terms: 30 + -30 = 0
0 + 1c = -4 + -30
1c = -4 + -30

Combine like terms: -4 + -30 = -34
1c = -34

Divide each side by '1'.
c = -34

Simplifying
c = -34

See similar equations:

| x(x-6)=391 | | 7x-1=4x-8(7+x) | | 0.16x+0.1y=0.08 | | 5x(12x-7)-4x(15x-11)=30+29x | | 30x=100+20x | | 3y+6x=36 | | 0.03x+0.09y=-0.27 | | 3(2f+4)=2(3-6) | | 3(5x+3)=36+6x | | -3x^2+7x+6=f(x) | | (x^3-27)(x^3-27)(x^3-27)=0 | | 5x(12x-7)-4x(15x-11)=30-29x | | -1/6(24)= | | 2/3(12)= | | 3c=2c+0 | | f(x)=-3x^2+7x+6 | | 0.15(x-4)=9.9-0.3(x-1) | | 2x+6=6x-6 | | ac+ax=b+6 | | 3=-6n+7n+18 | | 3d-14+6d+9= | | u^2=100 | | 3[a-5]=-6 | | 14+8x=-4+2x | | 4y-7+y+51=6y+50-4y | | x-1+6x=20 | | 3x+4y-7x-7y= | | 3m+(m+1)=6m+1 | | 3e(3e-10)=2 | | 9x(x+2y+3z)= | | 6s^3+23s^2+33s=13s | | 3x-5=5+3x |

Equations solver categories